VD_FINDINFO HC / 2012 / 618 vom 27. August 2012 - VD Tribunal cantonal (2012)
DIVORCE, AUTORITÉ PARENTALE, AUTORITÉ PARENTALE CONJOINTE, LIQUIDATION DU RÉGIME MATRIMONIAL, PARTICIPATION AUX ACQUÊTS | 133 CC, 204 al. 2 CC, 207 al. 1 CC, 163 Cst., 169 Cst., 191 Cst., 191c Cst., 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH)